Receding-Horizon Midcourse Guidance for Variable-Flow Ducted Rocket Missiles - Kim, Boseok; Jang, Jae-Il; Lee, Heunjae; Lee, Chang-Hun (IEEE transactions on aerospace and electronic systems, 2025)
This paper presents an optimization-based midcourse guidance methodology for variable-flow ducted rocket (VFDR) missiles. While classical trajectory optimization approaches are capable of addressing the inherent nonlinear dynamics and flight constraints involved in the midcourse guidance of VFDR missiles, their high computational demands may hinder their applicability for online guidance, which is crucial for air-to-air engagements. To overcome this challenge, this study proposes a formulation of the optimization problem based on the underlying principles of the receding horizon control (RHC) framework. Accordingly, the proposed formulation comprises a two-phase discretization scheme with distinct purposes: the first phase is designed to steer the system, while the second phase approximates the influence of the remaining trajectory, thereby significantly reducing computational complexity. In addition, an optimization algorithm is developed by integrating an improved trust-region method (ITRM) into the sequential convex programming (SCP) framework to achieve robust convergence performance. Numerical experiments demonstrate the suitability of the proposed optimization scheme for online implementation and validate the feasibility and robustness of the resulting online guidance method.